Local politics of Caluya Semirara coal corporation - Abasquez, Elizabeth B. (2001)
This study aims to trace and describe the history and character of local politics in Caluya, Antique; describe the dominant political families in the said municipality before and during the operations of the Semirara Coal Corporation; analyze the effects of the change in local administration to the management of the Semirara Coal Corporation; and determine the role played by the Semirara Coal Corporation in the conflict between dominant political families. This study finds that local politics in Caluya can be characterized as family-based and clanish in orientation. The dominant political families are the economic elite of the island, whose wealth is based on their vast track of land and diversified business ventures. These vast landholdings was the object of the perrenial land conflict that caused the breaking of one powerful family into two warring factions. The said land conflict matured into a fierce struggle for political supremacy. The traditional "guns, goons and gold" type of realpolitik is existent ., On the other hand, the change in local administration did not any way alter the operations of the Semirara Coal Corporation. The company gradually defined its role in the local politics of Caluya. Its role can be described in three phases. In the Janairo-Lim land conflict, the Semirara Coal Corporation did not play any part. The SCC employer-employee conflict signaled the second phase, which contributed to the defeat of former Mayor Oscar Lim and paved the way for the incumbent Mayor Nikita L. Frangue. The controversy over the Panian Project and the displaced SCC workers from Caluya ushered the third phase - the possible renewal of ties between the Lims and the SCC. The Semirara Coal Corporation has established itself as the ultimate prize of office.